Risk Factors for Major Adverse Cardiac Events Outcomes in Post Percutaneous Coronary Intervention during Index Admission - W. Isa, W. Yus Haniff; Muaath Ahmed Hasan Mohammed; Zulkefli Sanip; Zurkurnai Yusof (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Patients with ST-segment elevation myocardial infarction (STEMI) often undergo percutaneous coronary intervention (PCI) procedures during their index hospitalisation. However, some factors may increase the risk of major adverse cardiac event (MACE) outcomes after delaying PCI. We aimed to determine the risk factors for MACE outcomes in acute STEMI patients who had PCI during their index admission. Methods: In this retrospective single-center study, the medical records of STEMI patients who had PCI during their index hospitalisation in our facility were retrieved. At 30 days and six months post-PCI, demographic characteristics, clinical presentation, coronary risk factors, and the rate of MACE outcome were recorded and analysed. Results: This study included 91 STEMI patients. At 30 days and six months post-PCI, the rate of MACE was 10.5% and 8.0% respectively. At 30 days post-PCI, gender (p = 0.025), systolic blood pressure (p = 0.005) and heart rate (p = 0.003) were all associated with MACE outcomes. At six months, systolic blood pressure (p = 0.017), heart rate (p = 0.003), and previous coronary artery disease (CAD) (p = 0.014) were all associated with MACE. Conclusion: In acute STEMI patients, female gender, systolic blood pressure, heart rate, and a history of CAD are the risk factors for MACE outcomes after the PCI during the index admission. However, this is only single center study with short follow up period. Therefore, multi centers study and longer follow up period could provide better understanding on the factors associated with delayed PCI. REFERENCES Kumar A, Cannon CP. Acute coronary syndromes: diagnosis and management, part I. Mayo Clin Proc. 2009;84(10):917-38. doi: 10.1016/S0025-6196(11)60509-0. [Google Scholar][Pubmed][Crossref] O’Gara PT, Kushner FG, Ascheim DD, Casey DE Jr, Chung MK, de Lemos JA, et al. 2013 ACCF/AHA guideline for the management of ST-elevation myocardial infarction: a report of the American College of Cardiology Foundation/American Heart Association Task Force on Practice Guidelines. J Am Coll Cardiol. 2013;61(4):e78-e140. doi: 10.1016/j.jacc.2012.11.019.[<a href="https://scholar.google.com/scholar_lookup?title=O%27Gara+PT%2C+Kushner+FG%2C+Ascheim+DD%2C+Casey+DE+Jr%2C+Chung+MK%2C+de+Lemos+JA%2C+et+al.+2013+ACCF%2FAHA+guideline+for+the+management+of+ST-elevation+myocardial+infarction%3A+a+report+of+the+American+College+of+Cardiology+Foundation%2FAmerican+Heart+Association+Task+Force+on+Practice+Guidelines&btnG=">Google Scholar][Pubmed][Crossref] Ibanez B, James S, Agewall S, Antunes MJ, Bucciarelli-Ducci C, Bueno H, et al. 2017 ESC Guidelines for the management of acute myocardial infarction in patients presenting with ST-segment elevation: The Task Force for the management of acute myocardial infarction in patients presenting with ST-segment elevation of the European Society of Cardiology (ESC). Eur Heart J. 2018;39(2):119-77. doi: 10.1093/eurheartj/ehx393. [<a href="https://scholar.google.com/scholar_lookup?title=Ibanez+B%2C+James+S%2C+Agewall+S%2C+Antunes+MJ%2C+Bucciarelli-Ducci+C%2C+Bueno+H%2C+et+al.+2017+ESC+Guidelines+for+the+management+of+acute+myocardial+infarction+in+patients+presenting+with+ST-segment+elevation%3A+The+Task+Force+for+the+management+of+acute+myocardial+infarction+in+patients+presenting+with+ST-segment+elevation+of+the+European+Society+of+Cardiology+%28ESC%29.&btnG=">Google Scholar][Pubmed] Wan Ahmad WA. (Ed). Annual report of the NCVD-ACS registry, 2014 - 2015. Kuala Lumpur, Malaysia: National Cardiovascular Disease Database, 2017. Pollack C Jr. Pharmacological and mechanical revascularization strategies in STEMI: integration of the two approaches. J Invasive Cardiol. 2008;20(5):231-8. [Google Scholar] [Pubmed] Zeymer U, Ludman P, Danchin N, Kala P, Laroche C, Sadeghi M, et al. Reperfusion therapies and in-hospital outcomes for ST-elevation myocardial infarction in Europe: the ACVC-EAPCI EORP STEMI Registry of the European Society of Cardiology. Eur Heart J. 2021;42(44):4536-49. doi: 10.1093/eurheartj/ehab342. [<a href="https://scholar.google.com/scholar_lookup?title=Reperfusion+therapies+and+in-hospital+outcomes+for+ST-elevation+myocardial+infarction+in+Europe%3A+the+ACVC-EAPCI+EORP+STEMI+Registry+of+the+European+Society+of+Cardiology&btnG=">Google Scholar][Pubmed] Rathore SS, Curtis JP, Chen J, Wang Y, Nallamothu BK, Epstein AJ, et al. Association of door-to-balloon time and mortality in patients admitted to hospital with ST elevation myocardial infarction: national cohort study. BMJ. 2009;338:b1807. doi: 10.1136/bmj.b1807. [<a href="https://scholar.google.com/scholar_lookup?title=Association+of+door-to-balloon+time+and+mortality+in+patients+admitted+to+hospital+with+ST+elevation+myocardial+infarction%3A+national+cohort+study.&btnG=">Google Scholar] [PMC free article] [Pubmed] Boden WE, Eagle K, Granger CB. Reperfusion strategies in acute ST-segment elevation myocardial infarction: a comprehensive review of contemporary management options. J Am Coll Cardiol. 2007;50(10):917-29. doi: 10.1016/j.jacc.2007.04.084. [<a href="https://scholar.google.com/scholar_lookup?title=Boden+WE%2C+Eagle+K%2C+Granger+CB.+Reperfusion+strategies+in+acute+ST-segment+elevation+myocardial+infarction%3A+a+comprehensive+review+of+contemporary+management+options&btnG=">Google Scholar] [Pubmed][Crossref] McNamara RL, Herrin J, Wang Y, Curtis JP, Bradley EH, Magid DJ, et al. Impact of delay in door-to-needle time on mortality in patients with ST-segment elevation myocardial infarction. Am J Cardiol. 2007;100(8):1227-32. doi: 10.1016/j.amjcard.2007.05.043. [Google Scholar] [PMC free article] [Pubmed][Crossref] Kodera S, Morita H, Kiyosue A, Ando J, Komuro I. Cost-effectiveness of percutaneous coronary intervention compared with medical therapy for ischemic heart disease in Japan. Circ J. 2019;83(7):1498-1505. doi: 10.1253/circj.CJ-19-0148. [Google Scholar][Pubmed] Kip KE, Hollabaugh K, Marroquin OC, Williams DO. The problem with composite end points in cardiovascular studies: the story of major adverse cardiac events and percutaneous coronary intervention. J Am Coll Cardiol. 2008;51(7):701-7. doi: 10.1016/j.jacc.2007.10.034. [<a href="https://scholar.google.com/scholar_lookup?title=The+problem+with+composite+end+points+in+cardiovascular+studies%3A+the+story+of+major+adverse+cardiac+events+and+percutaneous+coronary+intervention&btnG=">Google Scholar][Pubmed][Crossref] Madhavan MV, Redfors B, Ali ZA, Prasad M, Shahim B, Smits PC, et al. Long-term outcomes after revascularization for stable ischemic heart disease. An individual patient-level pooled analysis of 19 randomized coronary stent trials. Circ Cardiovasc Interv. 2020;13:e008565. DOI: 10.1161/CIRCINTERVENTIONS.119.008565. [<a href="https://scholar.google.com/scholar_lookup?title=Long-term+outcomes+after+revascularization+for+stable+ischemic+heart+disease.+An+individual+patient-level+pooled+analysis+of+19+randomized+coronary+stent+trials&btnG=">Google Scholar][Pubmed][Crossref] Kosmidou I, Leon MB, Zhang Y, Serruys PW, von Birgelen C, Smits PC, et al. Long-term outcomes in women and men following percutaneous coronary intervention. J Am Coll Cardiol. 2020;75(14):1631-40. doi: 10.1016/j.jacc.2020.01.056. [Google Scholar][Pubmed][Crossref] Wong MYZ, Yap JJL, Chih HJ, Yan BPY, Fong AYY, Beltrame JF, et al. Regional differences in percutaneous coronary intervention outcomes in STEMI patients with diabetes: The Asia-Pacific evaluation of cardiovascular therapies (ASPECT) collaboration. Int J Cardiol. 2023;371:84-91. doi: 10.1016/j.ijcard.2022.10.001. [<a href="https://scholar.google.com/scholar_lookup?title=Regional+differences+in+percutaneous+coronary+intervention+outcomes+in+STEMI+patients+with+diabetes%3A+The+Asia-Pacific+evaluation+of+cardiovascular+therapies+%28ASPECT%29+collaboration&btnG=">Google Scholar][Pubmed][Crossref] Tsai IT, Wang CP, Lu YC, Hung WC, Wu CC, Lu LF, et al. The burden of major adverse cardiac events in patients with coronary artery disease. BMC Cardiovasc Disord. 2017;17(1):1. doi: 10.1186/s12872-016-0436-7. [<a href="https://scholar.google.com/scholar_lookup?title=Tsai+IT%2C+Wang+CP%2C+Lu+YC%2C+Hung+WC%2C+Wu+CC%2C+Lu+LF%2C+et+al.+The+burden+of+major+adverse+cardiac+events+in+patients+with+coronary+artery+disease&btnG=">Google Scholar][Pubmed] Rashid MK, Guron N, Bernick J, Wells GA, Blondeau M, Chong AY, et al. Safety and efficacy of a pharmacoinvasive strategy in ST-segment elevation myocardial infarction: A patient population study comparing a pharmacoinvasive strategy with a primary percutaneous coronary intervention strategy within a regional system. JACC: Cardiovasc Interv. 2016;9(19): 2014-20. doi: 10.1016/j.jcin.2016.07.004. [<a href="https://scholar.google.com/scholar_lookup?title=Safety+and+efficacy+of+a+pharmacoinvasive+strategy+in+ST-segment+elevation+myocardial+infarction%3A+A+patient+population+study+comparing+a+pharmacoinvasive+strategy+with+a+primary+percutaneous+coronary+intervention+strategy+within+a+regional+system&btnG=">Google Scholar][Pubmed][Crossref] Eagle KA, Goodman SG, Avezum A, Budaj A, Sullivan CM, López-Sendón J, et al. Practice variation and missed opportunities for reperfusion in ST-segment-elevation myocardial infarction: findings from the Global Registry of Acute Coronary Events (GRACE). Lancet. 2002;359(9304):373-7. doi: 10.1016/S0140-6736(02)07595-5. [<a href="https://scholar.google.com/scholar_lookup?title=Practice+variation+and+missed+opportunities+for+reperfusion+in+ST-segment-elevation+myocardial+infarction%3A+findings+from+the+Global+Registry+of+Acute+Coronary+Events+%28GRACE%29&btnG=">Google Scholar][Pubmed][Crossref] Scheller B, Hennen B, Hammer B, Walle J, Hofer C, Hilpert V, et al. Beneficial effects of immediate stenting after thrombolysis in acute myocardial infarction. J Am Coll Cardiol. 2003;42(4):634-41. doi: 10.1016/s0735-1097(03)00763-0. [Google Scholar][Pubmed][Crossref] Okkonen M, Havulinna AS, Ukkola O, Huikuri H, Pietilä A, Koukkunen H, et al. Risk factors for major adverse cardiovascular events after the first acute coronary syndrome. Ann Med. 2021;53(1):817-23. doi: 10.1080/07853890.2021.1924395. [Google Scholar] [Pubmed] Clinical Practice Guidelines. Management of Acute ST Segment Elevation Myocardial Infarction (STEMI) 2019, 4th National Heart Association of Malaysia. Antman EM, Hand M, Armstrong PW, Bates ER, Green LA, Halasyamani LK, et al. 2007 Focused update of the ACC/AHA 2004 guidelines for the management of patients with ST-elevation myocardial infarction: A report of the American College of Cardiology/American Heart Association task force on practice guidelines. Circulation. 2008;117(2):296-329. doi: 10.1161/CIRCULATIONAHA.107.188209. [<a href="https://scholar.google.com/scholar_lookup?title=Antman+EM%2C+Hand+M%2C+Armstrong+PW%2C+Bates+ER%2C+Green+LA%2C+Halasyamani+LK%2C+et+al.+2007+Focused+update+of+the+ACC%2FAHA+2004+guidelines+for+the+management+of+patients+with+ST-elevation+myocardial+infarction%3A+A+report+of+the+American+College+of+Cardiology%2FAmerican+Heart+Association+task+force+on+practice+guidelines&btnG=">Google Scholar] [Pubmed] Thygesen K, Alpert JS, Jaffe AS, Simoons ML, Chaitman BR, White HD, et al. ESC Committee for Practice Guidelines (CPG). Third universal definition of myocardial infarction. Eur Heart J. 2012;33(20):2551-67. doi: 10.1093/eurheartj/ehs184. [<a href="https://scholar.google.com/scholar_lookup?title=Thygesen+K%2C+Alpert+JS%2C+Jaffe+AS%2C+Simoons+ML%2C+Chaitman+BR%2C+White+HD%2C+et+al.+ESC+Committee+for+Practice+Guidelines+%28CPG%29.+Third+universal+definition+of+myocardial+infarction&btnG=">Google Scholar][Pubmed][Crossref] Zheng W, Yu CM, Liu J, Xie WX, Wang M, Zhang YJ, et al. Patients with ST-segment elevation of myocardial infarction miss out on early reperfusion: when to undergo delayed revascularization. J Geriatr Cardiol. 2017;14(8):524-31. doi: 10.11909/j.issn.1671-5411.2017.08.006. [Google Scholar] [PMC free article] [Pubmed] Bodí V, Rumiz E, Merlos P, Nunez J, López-Lereu MP, Monmeneu JV, et al. One-week and 6-month cardiovascular magnetic resonance outcome of the pharmacoinvasive strategy and primary angioplasty for the reperfusion of ST-segment elevation myocardial infarction. Revista Española de Cardiología (English Edition). 2011;64(2): 111-20. doi: 10.1016/j.rec.2010.10.010. [<a href="https://scholar.google.com/scholar_lookup?title=One-week+and+6-month+cardiovascular+magnetic+resonance+outcome+of+the+pharmacoinvasive+strategy+and+primary+angioplasty+for+the+reperfusion+of+ST-segment+elevation+myocardial+infarction&btnG=">Google Scholar][Pubmed][Crossref] Kanamasa K, Nakabayashi T, Hayashi T, Inoue Y, Ikeda A, Morii H, et al. Percutaneous transluminal coronary angioplasty performed 24-48 hours after the onset of acute myocardial infarction improves chronic-phase left ventricular regional wall motion. Angiology. 2000;51(4):281-8. doi: 10.1177/000331970005100402. [<a href="https://scholar.google.com/scholar_lookup?title=Percutaneous+transluminal+coronary+angioplasty+performed+24-48+hours+after+the+onset+of+acute+myocardial+infarction+improves+chronic-phase+left+ventricular+regional+wall+motion&btnG=">Google Scholar] [Pubmed] Cretu DE, Udroiu CA, Stoicescu CI, Tatu-Chitoiu G, Vinereanu D. Predictors of in-hospital mortality of ST-segment elevation myocardial infarction patients undergoing interventional treatment. An analysis of data from the RO-STEMI registry. Maedica (Bucur). 2015;10(4):295-303. [<a href="https://scholar.google.com/scholar_lookup?title=Predictors+of+in-hospital+mortality+of+ST-segment+elevation+myocardial+infarction+patients+undergoing+interventional+treatment.+An+analysis+of+data+from+the+RO-STEMI+registry&btnG=">Google Scholar] [PMC free article] [Pubmed] Chew DP, French J, Briffa TG, Hammett CJ, Ellis CJ, Ranasinghe I, et al. Acute coronary syndrome care across Australia and New Zealand: the SNAPSHOT ACS study. Med J Aust. 2013;199(3):185-91. doi: 10.5694/mja12.11854. [<a href="https://scholar.google.com/scholar_lookup?title=Chew+DP%2C+French+J%2C+Briffa+TG%2C+Hammett+CJ%2C+Ellis+CJ%2C+Ranasinghe+I%2C+et+al.+Acute+coronary+syndrome+care+across+Australia+and+New+Zealand%3A+the+SNAPSHOT+ACS+study&btnG=">Google Scholar][Pubmed] Granger CB, Goldberg RJ, Dabbous O, Pieper KS, Eagle KA, Cannon CP, et al. Predictors of hospital mortality in the global registry of acute coronary events. Arch Intern Med. 2003;163(19):2345-53. doi: 10.1001/archinte.163.19.2345. [<a href="https://scholar.google.com/scholar_lookup?title=Granger+CB%2C+Goldberg+RJ%2C+Dabbous+O%2C+Pieper+KS%2C+Eagle+KA%2C+Cannon+CP%2C+et+al.+Predictors+of+hospital+mortality+in+the+global+registry+of+acute+coronary+events&btnG=">Google Scholar] [Pubmed][Crossref] Rembek M, Goch A, Goch J. The clinical course of acute ST-elevation myocardial infarction in patients with hypertension. Kardiol Pol. 2010;68(2):157-63. [Google Scholar][Pubmed] Bundhun PK, Wu ZJ, Chen MH. Impact of modifiable cardiovascular risk factors on mortality after percutaneous coronary intervention: A systematic review and meta-analysis of 100 studies. Medicine (Baltimore). 2015;94(50):e2313. doi: 10.1097/MD.0000000000002313. [<a href="https://scholar.google.com/scholar_lookup?title=Impact+of+modifiable+cardiovascular+risk+factors+on+mortality+after+percutaneous+coronary+intervention%3A+A+systematic+review+and+meta-analysis+of+100+studies&btnG=">Google Scholar] [PMC free article] [Pubmed] Pong JZ, Ho AFW, Tan TXZ, Zheng H, Pek PP, Sia CH, et al. ST-segment elevation myocardial infarction with non-chest pain presentation at the Emergency Department: Insights from the Singapore Myocardial Infarction Registry. Intern Emerg Med. 2019;14(6): 989-97. doi: 10.1007/s11739-019-02122-3. [<a href="https://scholar.google.com/scholar_lookup?title=ST-segment+elevation+myocardial+infarction+with+non-chest+pain+presentation+at+the+Emergency+Department%3A+Insights+from+the+Singapore+Myocardial+Infarction+Registry&btnG=">Google Scholar][Pubmed] Radomska E, Sadowski M, Kurzawski J, Gierlotka M, Poloński L. ST-segment elevation myocardial infarction in women with type 2 diabetes. Diabetes Care. 2013;36(11):3469-75. doi: 10.2337/dc13-0394. [Google Scholar][Pubmed] Park KH, Ahn Y, Jeong MH, Chae SC, Hur SH, Kim YJ, et al. Different impact of diabetes mellitus on in-hospital and 1-year mortality in patients with acute myocardial infarction who underwent successful percutaneous coronary intervention: results from the Korean Acute Myocardial Infarction Registry. Korean J Intern Med. 2012;27(4):180-8. doi:10.3904/kjim.2012.27.2.180. [<a href="https://scholar.google.com/scholar_lookup?title=Different+impact+of+diabetes+mellitus+on+in-hospital+and+1-year+mortality+in+patients+with+acute+myocardial+infarction+who+underwent+successful+percutaneous+coronary+intervention%3A+results+from+the+Korean+Acute+Myocardial+Infarction+Registry&btnG=">Google Scholar] [PMC free article] [Pubmed] Ki YJ, Kang J, Yang HM, Woo Park K, Kang HJ, Koo BK, et al. Immediate compared with delayed percutaneous coronary intervention for patients with ST-segment-elevation myocardial infarction presenting ≥12 hours after symptom onset is not associated with improved clinical outcome. Circ Cardiovasc Interv. 2021;14(5):e009863. doi: 10.1161/CIRCINTERVENTIONS.120.009863. [<a href="https://scholar.google.com/scholar_lookup?title=Immediate+compared+with+delayed+percutaneous+coronary+intervention+for+patients+with+ST-segment-elevation+myocardial+infarction+presenting+%E2%89%A512+hours+after+symptom+onset+is+not+associated+with+improved+clinical+outcome&btnG=">Google Scholar] [Pubmed] Lee CY, Hairi NN, Wan Ahmad WA, Ismail O, Liew HB, Zambahari R, et al. Are there gender differences in coronary artery disease? The Malaysian National Cardiovascular Disease Database - Percutaneous Coronary Intervention (NCVD-PCI) Registry. PLoS One. 2013;8(2):e72382. doi: 10.1371/journal.pone.0072382. [<a href="https://scholar.google.com/scholar_lookup?title=Are+there+gender+differences+in+coronary+artery+disease%3F+The+Malaysian+National+Cardiovascular+Disease+Database+-+Percutaneous+Coronary+Intervention+%28NCVD-PCI%29+Registry&btnG=">Google Scholar] [PMC free article] [Pubmed] Guo Y, Yin F, Fan C, Wang Z. Gender difference in clinical outcomes of the patients with coronary artery disease after percutaneous coronary intervention: A systematic review and meta-analysis. Medicine (Baltimore). 2018;97(30):e11644. doi: 10.1097/MD.0000000000011644. [<a href="https://scholar.google.com/scholar_lookup?title=Gender+difference+in+clinical+outcomes+of+the+patients+with+coronary+artery+disease+after+percutaneous+coronary+intervention%3A+A+systematic+review+and+meta-analysis&btnG=">Google Scholar][Pubmed] Alexander KP, Newby LK, Cannon CP, Armstrong PW, Gibler WB, Rich MW, et al. Acute coronary care in the elderly, part I: Non-ST-segment-elevation acute coronary syndromes: a scientific statement for healthcare professionals from the American Heart Association Council on Clinical Cardiology: in collaboration with the Society of Geriatric Cardiology. Circulation. 2007;115(19):2549-69. doi: 10.1161/CIRCULATIONAHA.107.182615. [<a href="https://scholar.google.com/scholar_lookup?title=Acute+coronary+care+in+the+elderly%2C+part+I%3A+Non-ST-segment-elevation+acute+coronary+syndromes%3A+a+scientific+statement+for+healthcare+professionals+from+the+American+Heart+Association+Council+on+Clinical+Cardiology%3A+in+collaboration+with+the+Society+of+Geriatric+Cardiology&btnG=">Google Scholar] [Pubmed] Bueno H, Betriu A, Heras M, Alonso JJ, Cequier A, García EJ, et al. Primary angioplasty vs. fibrinolysis in very old patients with acute myocardial infarction: TRIANA (TRatamiento del Infarto Agudo de miocardio eN Ancianos) randomized trial and pooled analysis with previous studies. Eur Heart J. 2011;32(1):51-60. doi: 10.1093/eurheartj/ehq375.[<a href="https://scholar.google.com/scholar_lookup?title=Primary+angioplasty+vs.+fibrinolysis+in+very+old+patients+with+acute+myocardial+infarction%3A+TRIANA+%28TRatamiento+del+Infarto+Agudo+de+miocardio+eN+Ancianos%29+randomized+trial+and+pooled+analysis+with+previous+studies&btnG=">Google Scholar] [PMC free article] [Pubmed] Claessen BE, Kikkert WJ, Engstrom AE, Hoebers LP, Damman P, Vis MM, et al. Primary percutaneous coronary intervention for ST elevation myocardial infarction in octogenarians: trends and outcomes. Heart. 2010;96(11):843-7. doi: 10.1136/hrt.2009.185678. [Google Scholar][Pubmed] Chen X, Li M, Jiang H, Li Y, Mo J, Lin P, et al. STEMI outcomes in Guangzhou and Hong Kong: Two-centre retrospective interregional study. PLoS One. 2016;11(3):e0149981. doi: 10.1371/journal.pone.0149981. [Google Scholar] [PMC free article] [Pubmed] Caretta G, Passamonti E, Pedroni PN, Fadin BM, Galeazzi GL, Pirelli S. Outcomes and predictors of mortality among octogenarians and older with ST-segment elevation myocardial infarction treated with primary coronary angioplasty. Clin Cardiol. 2014;37(9):523-9. doi:10.1002/clc.22313. [<a href="https://scholar.google.com/scholar_lookup?title=Outcomes+and+predictors+of+mortality+among+octogenarians+and+older+with+ST-segment+elevation+myocardial+infarction+treated+with+primary+coronary+angioplasty&btnG=">Google Scholar] [PMC free article] [Pubmed] Bordejevic DA, Caruntu F, Mornos C, Olariu I, Petrescu L, Tomescu MC, et al. Prognostic impact of blood pressure and heart rate at admission on in-hospital mortality after primary percutaneous intervention for acute myocardial infarction with ST-segment elevation in western Romania. Ther Clin Risk Manag. 2017;13:1061-68. https://doi.org/10.2147/TCRM.S141312. [<a href="https://scholar.google.com/scholar_lookup?title=Prognostic+impact+of+blood+pressure+and+heart+rate+at+admission+on+in-hospital+mortality+after+primary+percutaneous+intervention+for+acute+myocardial+infarction+with+ST-segment+elevation+in+western+Romania&btnG=">Google Scholar] [PMC free article] [Pubmed] Labib S, Kassem HH, Kandil H. Peri-procedural blood pressure changes and their relationship with mace in patients undergoing percutaneous coronary intervention: a cross-sectional study. Integr Blood Press Control. 2020;13:187-95. doi: 10.2147/IBPC.S268848. [<a href="https://scholar.google.com/scholar_lookup?title=Peri-procedural+blood+pressure+changes+and+their+relationship+with+mace+in+patients+undergoing+percutaneous+coronary+intervention%3A+a+cross-sectional+study&btnG=">Google Scholar] [PMC free article] [Pubmed] Montalescot G, Dallongeville J, Van Belle E, Rouanet S, Baulac C, Degrandsart A, et al. STEMI and NSTEMI: are they so different? 1 year outcomes in acute myocardial infarction as defined by the ESC/ACC definition (the OPERA registry). Eur Heart J. 2007;28(12):1409-17. doi: 10.1093/eurheartj/ehm031. [<a href="https://scholar.google.com/scholar_lookup?title=STEMI+and+NSTEMI%3A+are+they+so+different%3F+1+year+outcomes+in+acute+myocardial+infarction+as+defined+by+the+ESC%2FACC+definition+%28the+OPERA+registry%29&btnG=">Google Scholar][Pubmed] Khoury H, Lavoie L, Welner S, Folkerts K. The Burden of Major Adverse Cardiac Events and Antiplatelet Prevention in Patients with Coronary or Peripheral Arterial Disease. Cardiovasc Ther. 2016;34(2):115-24. doi: 10.1111/1755-5922.12169. [Google Scholar][Pubmed] Farhadian M, Dehdar Karsidani S, Mozayanimonfared A, Mahjub H. Risk factors associated with major adverse cardiac and cerebrovascular events following percutaneous coronary intervention: a 10-year follow-up comparing random survival forest and Cox proportional-hazards model. BMC Cardiovasc Disord 21, 38 (2021). https://doi.org/10.1186/s12872-020-01834-1. [<a href="https://scholar.google.com/scholar_lookup?title=Risk+factors+associated+with+major+adverse+cardiac+and+cerebrovascular+events+following+percutaneous+coronary+intervention%3A+a+10-year+follow-up+comparing+random+survival+forest+and+Cox+proportional-hazards+model&btnG=">Google Scholar] [PMC free article] [Pubmed]